2020
DOI: 10.12965/jer.2040656.328
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of high-volume compared to low-volume resistance exercise on lung function

Abstract: The aim of this study was to examine whether a high-volume compared to low-volume resistance exercise session acutely impairs lung function. Fourteen males (age 23.8± 6.5 years) with resistance training experience participated in this study. Participants completed two resistance training protocols (high-and low-volume) and a control session (no exercise) with the sequence randomised. High-and low-volume sessions involved 5 sets (5-SETS) and 2 sets (2-SETS), respectively of 10 repetitions at 65% one-repetition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…As the volume of resistance training increases, the respiratory system faces a substantial demand due to heightened metabolic stress. This was demonstrated by Hackett et al [ 22 ], where performing five sets versus two sets across various resistance exercises resulted in an increased hyperventilatory response, evident through decreases in PETCO 2 . Notably, all sets in our study were executed to volitional fatigue, with the concentric phase performed at maximal concentric velocity.…”
Section: Discussionmentioning
confidence: 86%
“…As the volume of resistance training increases, the respiratory system faces a substantial demand due to heightened metabolic stress. This was demonstrated by Hackett et al [ 22 ], where performing five sets versus two sets across various resistance exercises resulted in an increased hyperventilatory response, evident through decreases in PETCO 2 . Notably, all sets in our study were executed to volitional fatigue, with the concentric phase performed at maximal concentric velocity.…”
Section: Discussionmentioning
confidence: 86%
“…It is known that metabolic stress causes hyperventilation, resulting in a higher level of end-tidal CO 2 in each exhalation (24). Furthermore, protocols leading to failure result in a greater load volume, and it has been suggested that a high-volume session entails higher metabolic stress due to the lower end-tidal CO 2 partial pressure in comparison with a low-volume session (10). The higher local metabolic stress from Viana-Rosa's study in comparison with our study may have caused a higher hyperventilation that could be restricted by a FFP2 mask, which did not occur in our study for 2 plausible reasons: (a) They completed almost 60 repetitions of BP during the medium-intensity session (i.e., 50% 1RM), whereas our subjects completed a similar volume as a result of summing the repetitions performed during BP and SQ and failure was only reached by some subjects during the last set of each exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The great demands placed on the respiratory system during intense aerobic exercise have been documented in runners, with lung function being acutely impaired following marathon and ultra-marathon events [ 15 ]. In comparison, there does not seem to be any detrimental acute change in lung function following resistance training [ 16 ] and this lack of training stimulus on the lungs likely explains the similar lung function observed between strength/power athletes and sedentary adults [ 10 ]. However, unique respiratory system adaptations appear to take place within strength-trained athletes, as reported by Brown et al [ 17 ], with greater diaphragm mass and respiratory muscle strength in world-class male powerlifters compared to untrained healthy adults.…”
Section: Introductionmentioning
confidence: 99%